Spectroscopic Studies of Interaction of Protein with Cerium Oxide Nanoparticles - Abraham, Suja (Asian Journal of Chemistry, 2018)
In anticancer therapy research, metal oxide nanoparticles are used experimentally to directly kill tumor cells in vitro and in vivo. Cerium oxide nanoparticles can be used to treat cancer and several other diseases. Structural changes of adsorbed protein are necessary for cellular uptake of nanoparticles. Therefore, in order to find structural changes of bovine serum albumin (BSA) when it interacts with cerium oxide nanoparticles spectroscopic studies were conducted.The changes in fluorescence emission parameters of bovine serum albumin with increasing concentrations of cerium oxide nanoparticles indicated minor conformational changes in the structure of bovine serum albumin.